2014
DOI: 10.1371/journal.pone.0087497
|View full text |Cite
|
Sign up to set email alerts
|

Associations of MTHFR Gene Polymorphisms with Hypertension and Hypertension in Pregnancy: A Meta-Analysis from 114 Studies with 15411 Cases and 21970 Controls

Abstract: BackgroundSeveral epidemiological studies have investigated the associations of methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms with hypertension (H) or hypertension in pregnancy (HIP). However, the results were controversial. We therefore performed a comprehensive meta-analysis to provide empirical evidences on the associations.MethodologiesThe English and Chinese databases were systematically searched to identify relevant studies. Odds ratios (ORs) and 95% confidence intervals (CIs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 107 publications
3
83
0
Order By: Relevance
“…It has been suggested that an accumulation of 10-formyl tetrahydrofolate in endothelial cells may affect folate metabolism and in turn affect endothelial NO synthase activity (105) . Therefore, riboflavin may enhance endothelial NO synthase activity by correcting the imbalance in methylated v. non-methylated tetrahydrofolate in (117) 1520 cases Chinese 1·87 (1·31, 2·68) 1334 controls Yang et al (4) 6584 cases Worldwide 1·36 (1·20, 1·53) 6760 controls Wu et al (118) 5207 cases Worldwide 1·62 (1·32, 1·99) 5383 controls Yang et al (119) those with the TT genotype or by increasing 5-methyltetrahydrofolate and thus decreasing BP irrespective of BP-lowering drugs (105) . Further work is required to investigate mechanisms linking this polymorphism with BP and the potential for riboflavin to provide a targeted option to treat elevated BP in this genotype group.…”
Section: Mechanism Of Mthfr C677t Polymorphism Riboflavin and Blood mentioning
confidence: 99%
“…It has been suggested that an accumulation of 10-formyl tetrahydrofolate in endothelial cells may affect folate metabolism and in turn affect endothelial NO synthase activity (105) . Therefore, riboflavin may enhance endothelial NO synthase activity by correcting the imbalance in methylated v. non-methylated tetrahydrofolate in (117) 1520 cases Chinese 1·87 (1·31, 2·68) 1334 controls Yang et al (4) 6584 cases Worldwide 1·36 (1·20, 1·53) 6760 controls Wu et al (118) 5207 cases Worldwide 1·62 (1·32, 1·99) 5383 controls Yang et al (119) those with the TT genotype or by increasing 5-methyltetrahydrofolate and thus decreasing BP irrespective of BP-lowering drugs (105) . Further work is required to investigate mechanisms linking this polymorphism with BP and the potential for riboflavin to provide a targeted option to treat elevated BP in this genotype group.…”
Section: Mechanism Of Mthfr C677t Polymorphism Riboflavin and Blood mentioning
confidence: 99%
“…The NOS consists of three parts with nine items (one point for each item): selection of the study groups (four items), comparability of the groups (two items), and outcome measurements (three items) [21]. A score greater than 5 was regarded as high quality; otherwise, the study was considered low quality [22].…”
Section: Quality Evaluationmentioning
confidence: 99%
“…The above results were conflicting or inconclusive, presumably due to various genetic backgrounds, small sample size and potential confounding bias. Meta-analysis is a widely used statistical method in medical studies, particularly for a topic that are being extensively studied with controversial results [31]. Thus, we performed a meta-analysis to provide a more comprehensive assessment of the association between this polymorphism and ADHD.…”
Section: Introductionmentioning
confidence: 99%